BLACK HOLE X-RAY BINARIES - Cherepashchuk, A. M. (Одеські астрономічні публікації, 2017)
Masses of black holes in 13 X-ray binary systems determined by different authors are summarized and compared with those of WR stars in close binary systems, which can be considered as progenitors of relativistic objects. Average mass of CO cores of WR stars is ∼ (8 - 12) MSunwhich is close to that of black holes ∼ (8 - 10) MSun. Distribution of masses of WR stars MWR = 5 - 55 MSun is continuous but not bimodal in contrast with distribution of masses of neutron stars (MNS = 1.35 ± 0.15 MSun ) and black holes (MBH ≈ 8 ÷ 10 MSun).